2022
DOI: 10.1055/s-0041-1740803
|View full text |Cite
|
Sign up to set email alerts
|

Auto-aggressive CXCR6+ CD8 T cells cause liver immune pathology in NASH

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
2
12
1
Order By: Relevance
“…One example is eATP, which can be released actively through exporting channels, such as pannexin-1 (43,44), or passively by dying cells due to local or systemic inflammation and tissue damage (23). One eATP sensor in particular (P2RX7) is expressed at high levels and plays relevant roles in controlling CD8 1 T cell responses (24,25,45,46). Because eATP can be released actively or passively, it is possible that CD8 1 T cells are exposed to this signal not only at sites of active viral infection but also in secondary lymphoid organs during initial effector function.…”
Section: Discussionmentioning
confidence: 99%
“…One example is eATP, which can be released actively through exporting channels, such as pannexin-1 (43,44), or passively by dying cells due to local or systemic inflammation and tissue damage (23). One eATP sensor in particular (P2RX7) is expressed at high levels and plays relevant roles in controlling CD8 1 T cell responses (24,25,45,46). Because eATP can be released actively or passively, it is possible that CD8 1 T cells are exposed to this signal not only at sites of active viral infection but also in secondary lymphoid organs during initial effector function.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic derangement in NASH also induces T cell pathology. Notably, CXCR6 + CD8 + T cells acquire hepatocyte killing activity in response to increased levels of the short-chain fatty acid acetate ( 136 ). Accordingly, depletion of T lymphocyte populations or disruption of their signaling activity is protective ( 115 , 133 , 137 ).…”
Section: Hscs and Immunity In Nashmentioning
confidence: 99%
“…The scar-associated macrophage identified by Ramachandran et al has also been suggested to be of bone marrow origin. 30 34 Therefore, it is becoming evident that bone marrow–derived macrophages exhibit a pathogenic phenotype in NASH pathology.…”
Section: Macrophages/dcsmentioning
confidence: 99%
“…More recently, the details of CD8 T cells in a CD-HFD-induced NASH model have been investigated. 34 CD8 T cells that accumulate in the liver in NASH have a liver-resident phenotype of CXC chemokine receptor (CXCR) 6+ and are tissue resident memory (Trm)-like cells that are maintained and activated by IL-15. This led to the new concept that human and mouse CD8 Trm-like cells acquire an autoaggressive phenotype that exerts cytotoxic activity independently of MHC class I via acetate and ATP-P2 × 7 signaling.…”
Section: Cd8 T Cells/nkt Cells/nk Cellsmentioning
confidence: 99%
See 1 more Smart Citation